PERANCANGAN PRODUK FURNITUR INTERIOR DAN BOOTH DENGAN PENDEKATAN PRINSIP MINIMALIS OLEH NIW - Wijaya, Yehezkiel Nugraha Ivan; Nuradhi, Maureen; Rahadiyanti, Melania (Aksen : Journal of Design and Creative Industry, 2020)
The pace of the economy in Indonesia faces an era of shifting where many new businesses take advantageof this opportunity. The rapid growth of the Indonesian economy brings opportunities to various aspects ofpeople’s lives, both from the pattern of the use of money to the opportunity to open a business. One of thecontributors to Indonesia’s economic growth is the creative economy. Indonesia’s creative economy hasbecome a promising new business opportunity, which is now also being cultivated by the community. Theproduct and furniture industry is one of the 16 sectors of Indonesia’s creative economy. NIW an online ore-commerce based company has a share of the mass market where the company provides various needsfor home furniture and interior accessories. The company carries a minimalist concept where the minimalistphilosophy reflects an awareness of maximizing the consumption of goods by minimizing various componentsthat are not needed. A minimalist visual form is expected to change the perspective and lifestyle of its users inbetween the complexities that often distract human thoughts and feelings in everyday life. Before the productis released to the market, the company makes a market reset so that the goods made can be accepted bythe public. In addition to designing furniture, to support business activities a booth is needed as a mediacampaign. The booth on the NIW company is useful as a medium for exhibiting product results and is alsoa media space where prospective customers can feel, see, and feel directly for each product in order tounderstand and adjust the user’s tastes. The company collaborates with other creative industry personalitiesin various fields and several non competitor brands. Keywords: Collaboration, E-Commerce, Furniture, Minimalist, Product Design.